White Matter Hyperintensities of Bilateral Lenticular Putamen in Patients with Proliferative Diabetic Retinopathy: A Voxel‐based Morphometric Study - Xiao A (Dove Medical Press, 2021)
Ang Xiao,1,* Qian-Min Ge,1,* Hui-Feng Zhong,2 Li-Juan Zhang,1 Hui-Ye Shu,1 Rong-Bin Liang,1 Yi Shao,1 Qiong Zhou1 1Department of Ophthalmology, The First Affiliated Hospital of Nanchang University, Jiangxi Province Ocular Disease Clinical Research Center, Nanchang, Jiangxi, 330006, People’s Republic of China; 2Department of Intensive Care, The First Affiliated Hospital of Gannan Medical University, Ganzhou, Jiangxi, 341000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Shao; Qiong ZhouDepartment of Ophthalmology, The First Affiliated Hospital of Nanchang University, Jiangxi Province Ocular Disease Clinical Research Center, No. 17, YongWaiZheng Street, DongHu District, Nanchang, 330006, Jiangxi, People’s Republic of ChinaTel/Fax +86 791-88692520; +86 791-88694639Email freebee99@163.com; qiongz-ms@126.comObjective: To explore the changes in gray matter volume (GMV) and white matter volume (WMV) in proliferative diabetic retinopathy (PDR) patients using voxel-based morphometry (VBM).Participants and Methods: In total, 15 patients (10 males, 5 females) with PDR were enrolled to the patient group and 15 healthy controls (10 males, 5 females) to the control group, matched for age, sex, handedness, and education status. All individuals underwent voxel-based morphometry scans. GMV and WMV were compared between the two groups.Results: GMV in bilateral superior temporal gyrus, sixth area of left cerebellum, left middle temporal gyrus, left orbital inferior frontal gyrus and left middle cingulum gyrus and WMV in left thalamus and left precuneus were significantly lower in patients than controls (P< 0.01). Conversely, WMV was significantly higher in bilateral lenticular putamen of patients than controls (P< 0.01).Conclusion: Abnormal GMV and WMV in many specific areas of the cerebrum provide new insights for exploration of the occurrence and development of DR and its pathophysiology.Keywords: voxel-based morphometric, white matter, gray matter, proliferative diabetic retinopathy